(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
The landscape of language education has transformed significantly in the digital age, necessitating modern approaches to teaching languages, especially for philology students. This article explores contemporary methodologies, integrating technology, and innovative pedagogical strategies to enhance language learning for philology students. Emphasis is placed on interactive and collaborative techniques, the use of digital tools, and the importance of cultural immersion.